Serum Interleukin-6 in Patients with Burning Mouth Syndrome and Relationship with Depression and Perceived Pain - Qianming Chen; Juan Xia; Mei Lin; Hongmei Zhou; Bingqi Li (Mediators of Inflammation)
Objective. To examine alteration of serum interleukin-6 and its clinical significance in burning mouth syndrome (BMS) patients. Methods. 48 BMS patients and 31 healthy controls participated in the study. Serum interleukin-6 was measured by means of ELISA. Hamilton rating scale of depression (HRSD) and visual analogue scale (VAS) were used to quantitiate depressive status and pain levels of subjects, respectively. Results. 15 (31%) patients displayed substantial depressive symptoms (HRSD ≧16). HRSD scores of patients were significantly higher than controls and positively correlated to their VAS values (P=.002). Serum interleukin-6 in patients was much lower than controls and negatively correlated to their VAS values (P=.011). However, no significant relations were found between interleukin-6 and HRSD scores (P=.317). Conclusions. Serum interleukin-6 in patients with burning mouth syndrome is decreased and negatively correlated to chronic pain. Both psychological and neuropathic disorders might act as precipitating factors in BMS etiopathogenesis.